THE COMPLEXITY OF ASSESSING THE LEVEL OF ECONOMIC SECURITY OF INNOVATION-ORIENTED SOCIO-ECONOMIC SYSTEMS - NYZHNYK, Oleh; NYZHNYK, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The current macroeconomic and socio-political situation in Ukraine is extremely complicated by a long period of economic decline, the consequences of the pandemic and the conduct of a full-scale war, which actualizes the issue of maintaining an adequate level of economic security of socio-economic systems and, including, the issue of improving approaches to assessing its current level. The evaluation and analytical processes are one of the most important in the system of ensuring the economic security of socio-economic systems of different hierarchical levels, since, under the conditions of qualitative construction and methodology, they allow not only to evaluate the current situation with the level of economic security, but also to establish a complex of positive and negative factors impact on it and simulate various scenarios of changes in the level of economic security in the nearest and strategic perspectives under their influence. In view of this, the issues of comprehensive assessment of the level of economic security of modern socio-economic systems become particularly acute and actualize the need for their in-depth study. The purpose of the study is to develop approaches to comprehensive assessment of the level of economic security of innovation-oriented socio-economic systems. In the article highlighted the approaches to considering the essence and features of socio-economic systems as a whole and innovation-oriented socio-economic systems as their variety. Carried out the analysis of the fundamental characteristics of socio-economic systems. Substantiated the importance of building highly effective mechanisms for managing the economic security of socio-economic systems of Ukraine in the context of crisis macroeconomic processes and military operations on its territory. Studied the existing approaches to the assessment of economic security with the determination of their shortcomings in the context of ensuring the comprehensiveness of the assessment. Determined the list of key characteristics of the innovation-oriented socio-economic system, which should serve as the basis for the development of a comprehensive methodology for assessing their economic security, and the need to use the spectrum of economic interests of the studied systems in the assessment approach.